Parameters Governing the Community Structure and Element Turnover in Kermadec Volcanic Ash and Hydrothermal Fluids as Monitored by Inorganic Electron Donor Consumption, Autotrophic CO2 Fixation and 16S Tags of the Transcriptome in Incubation Experiments - Böhnke, Stefanie; Sass, Katharina; Gonnella, Giorgio; Diehl, Alexander; Kleint, Charlotte; Bach, Wolfgang; Zitoun, Rebecca; Koschinsky, Andrea; Indenbirken, Daniela; Sander, Sylvia G.; Kurtz, Stefan; Perner, Mirjam (Frontiers in Microbiology, 2019)
The microbial community composition and its functionality was assessed for hydrothermal fluids and volcanic ash sediments from Haungaroa and hydrothermal fluids from the Brothers volcano in the Kermadec island arc (New Zealand). The Haungaroa volcanic ash sediments were dominated by epsilonproteobacterial Sulfurovum sp.. Ratios of electron donor consumption to CO2 fixation from respective sediment incubations indicated that sulfide oxidation appeared to fuel autotrophic CO2 fixation, coinciding with thermodynamic estimates predicting sulfide oxidation as the major energy source in the environment. Transcript analyses with the sulfide-supplemented sediment slurries demonstrated that Sulfurovum prevailed in the experiments as well. Hence, our sediment incubations appeared to simulate environmental conditions well suggesting that sulfide oxidation catalyzed by Sulfurovum members drive biomass synthesis in the volcanic ash sediments. For the Haungaroa fluids no inorganic electron donor and responsible microorganisms could be identified that clearly stimulated autotrophic CO2 fixation. In the Brothers hydrothermal fluids Sulfurimonas (49%) and Hydrogenovibrio/Thiomicrospira (15%) species prevailed. Respective fluid incubations exhibited highest autotrophic CO2 fixation if supplemented with iron(II) or hydrogen. Likewise catabolic energy calculations predicted primarily iron(II) but also hydrogen oxidation as major energy sources in the natural fluids. According to transcript analyses with material from the incubation experiments Thiomicrospira/Hydrogenovibrio species dominated, outcompeting Sulfurimonas. Given that experimental conditions likely only simulated environmental conditions that cause Thiomicrospira/Hydrogenovibrio but not Sulfurimonas to thrive, it remains unclear which environmental parameters determine Sulfurimonas’ dominance in the Brothers natural hydrothermal fluids.